Seasonality at the clinical onset of type 1 diabetes—Lessons from the SWEET database. (October 2016) - Gerasimidi Vazeou, A.; Kordonouri, O.; Witsch, M.; Hermann, J.M.; Forsander, G.; de Beaufort, C.; Veeze, H.J.; Maffeis, C.; Cherubini, V.; Cinek, O.; Piccini, B.; Holl, R.W.; et al.
Abstract : Background: Seasonality at the clinical onset of type 1 diabetes (T1D) has been suggested by different studies, however, the results are conflicting. This study aimed to evaluate the presence of seasonality at clinical onset of T1D based on the SWEET database comprising data from 32 different countries. Methods: The study cohort included 23 603 patients (52% males) recorded in the international multicenter SWEET database (48 centers), with T1D onset ≤20 years, year of onset between 1980 and 2015, gender, year and month of birth and T1D‐diagnosis documented. Data were stratified according to four age groups (<5, 5‐<10, 10‐<15, 15‐20 years) at T1D onset, the latitude of European center (Northern ≥50°N and Southern Europe <50°N) and the year of onset ≤ or >2009. Results: Analysis by month revealed significant seasonality with January being the month with the highest and June with the lowest percentage of incident cases ( P < .001). Winter, early spring and late autumn months had higher percentage of incident cases compared with late spring and summer months. Stratification by age showed similar seasonality patterns in all four age groups ( P ≤ .003 each), but not in children <24 months of age. There was no gender or latitude effect on seasonality pattern, however, the pattern differed by the year of onset ( P < .001). Seasonality of diagnosis conformed to a sinusoidal model for all cases, females and males, age groups, northern and southern European countries. Conclusions: Seasonality at T1D clinical onset is documented by the large SWEET database with no gender or latitude (Europe only) effect except from the year of manifestation.